Multi-Level Decision Making Models, Methods and Applications - Zhang, Guangquan (Springer, 2015)
Multi-level decision-making (MLDM) handles problems that require compromise between the objectives of two or more interacting entities which are arranged within a hierarchical structure with independent and perhaps conflicting objectives. Bi level decision-making is a special and particularly popular case of MLDM, in which only two levels of decision entities are involved, each of which tries to optimize their individual objectives under certain constraints, and to act and react in a sequential manner. The MLDM problem appears naturally in critical resource management, production and transportation planning, and organizational policy making. There are two fundamental issues to address in dealing with an MLDM problem. One is how to model a multi-level decision problem, and the other is how to find an optimal solution to the problem...